2018
DOI: 10.1186/s12870-017-1217-x
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of alternative splicing among the multiple tissues in cucumber

Abstract: BackgroundAlternative splicing (AS) is an important post-transcriptional process. It has been suggested that most AS events are subject to tissue-specific regulation. However, the global dynamics of AS in different tissues are poorly explored.ResultsTo analyse global changes in AS in multiple tissues, we identified the AS events and constructed a comprehensive catalogue of AS events within each tissue based on the genome-wide RNA-seq reads from ten tissues in cucumber. First, we found that 58% of the multi-exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…For most of the differentially spliced regions, both forms were 440 present, and the difference in relative abundance between forms was often slight, rarely more 441 than five or ten percent ( Supplementary Table S1). Our data supports the growing body of 442 evidence that alternative splicing is cell, tissue, and stage specific in plants (Vitulo et al, 2014;443 Gupta et al, 2015;Li et al, 2016a;Sun et al, 2018), including in roots (Li et al, 2016b). It is 444 likely that alternative splicing plays a role in fine-tuning gene function to meet the needs of 445 different plant tissues or cell types where a gene is expressed.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…For most of the differentially spliced regions, both forms were 440 present, and the difference in relative abundance between forms was often slight, rarely more 441 than five or ten percent ( Supplementary Table S1). Our data supports the growing body of 442 evidence that alternative splicing is cell, tissue, and stage specific in plants (Vitulo et al, 2014;443 Gupta et al, 2015;Li et al, 2016a;Sun et al, 2018), including in roots (Li et al, 2016b). It is 444 likely that alternative splicing plays a role in fine-tuning gene function to meet the needs of 445 different plant tissues or cell types where a gene is expressed.…”
supporting
confidence: 88%
“…SR transcripts 66 themselves are also highly alternatively spliced in plants, with the relative abundance of these 67 alternative transcripts varying according to environmental stresses and hormones (Palusa et al, 68 2007;Gulledge et al, 2012;Filichkin et al, 2015a;Keller et al, 2016;Mei et al, 2017). 69 A growing body of evidence indicates that cell and tissue specific regulation of alternative 70 splicing occurs in plants, but its significance and extent is not well established (Vitulo et al, 71 2014;Li et al, 2016a;Sun et al, 2018). We previously found through analysis of RNA-Seq data 72 from Arabidopsis pollen that the relative abundance of splice variants was similar between 73 leaves and pollen, despite the differences between the two tissues (Loraine et al, 2013).…”
mentioning
confidence: 99%
“…9a). Previous studies indicated that alternative spliced transcripts have tissue-specific expression in various plants [61][62][63][64]. For novel splice junctions in B. rapa, 34.4% of alternative spiced transcripts were detected in only one tissue [45].…”
Section: Discussionmentioning
confidence: 96%
“…sativus cv. 9930, we assembled transcripts by using TopHat and Cufflinks [16], respectively. These sets of transcripts were then compared with the reference genome annotation file using Cuffcompare.…”
Section: Identification Of Alternative Splicing Events and Isoformsmentioning
confidence: 99%